An Approach for DDoS Attack Prevention in Mobile ad hoc Networks - Timcenko, V. V. (Elektronika ir Elektrotechnika, 2014)
In this paper we propose a prevention mechanism for distributed denial of service (DDoS) attacks in Mobile Ad hoc Networks (MANET) environment. Since MANETs are wireless, self-configuring networks with highly unpredictable node movement, the security provisioning represents one of the most sensitive issues. The presented approach relies on the investigation of widespread bandwidth attacks, with focus on Distributed Denial of Service (DDoS) attacks, which are extremely dangerous, hard to detect and challenging to prevent. DDoS represents a coordinated activity of a group of attackers aiming to prevent legitimate users the access to network resources. Intrusion prevention systems (IPS) are mainly considered as extensions of intrusion detection systems (IDS) with a purpose to actively prevent and block intrusions that are detected by IDS. The presented IPS model is based on the analysis of the forensic analysis report generated by IDS incorporated into the network security monitoring system. DOI: http://dx.doi.org/10.5755/j01.eee.20.6.7289